Development of a forensic glass database system employing refractive index measurement - Nur Fazidah Asmuje @ Asmuzi, 1987-; Umi Kalthom Ahmad, supervisor; Roliana Ibrahim, supervisor; Nor Ummiza Kamaruzaman; Fakulti sains (2012)
Thesis (Sarjana Sains (Sains Forensik)) - Universiti Teknologi Malaysia, 2012